PEDAGOGICAL METHODS OF TEACHING ENGLISH LANGUAGE TO PRIMARY STUDENTS (Scientific journal of the Fergana State University, 2023)
In the article, today's unique approaches to teaching English to young children, effective use of age-appropriate methods for teaching the language, and innovative ways of teaching are described in detail. The changes taking place in the field of education in our country today can be said to be the fruit of development based on the positive results achieved. At this point, the result of the reforms implemented in the education system is extremely significant.